Integrative evidence construction for resveratrol treatment of nonalcoholic fatty liver disease: preclinical and clinical meta-analyses - He, Xuan; Li, Yubing; Deng, Xinyu; Xiao, Xiaolin; Zeng, Jinhao (Frontiers in Pharmacology, 2023)
Background: Resveratrol, a polyphenol found in various plants, is known for its diverse bioactivities and has been explored in relation to nonalcoholic fatty liver disease (NAFLD).However, no high-quality evidence exists regarding its efficacy.Objective: a meta-analysis was conducted to evaluate the potential efficacy of resveratrol in treating NAFLD by analyzing both preclinical studies and clinical trials.Method: PubMed, Embase and Web of Science were searched for the included literature with the criteria for screening. Quantitative synthesis and meta-analyses were performed by STATA 16.0.Twenty-seven studies were included, and the results indicated that resveratrol effectively improved liver function, reduced fatty liver indicators, and affected other indices in preclinical studies. The effective dosage ranged from 50 mg/kg-200 mg/kg, administered over a period of 4-8 weeks. While there were inconsistencies between clinical trials and preclinical research, both 2 study types revealed that resveratrol significantly reduced tumor necrosis factor-α levels, further supporting its protective effect against NAFLD. Additionally, resveratrol alleviated NAFLD primarily via AMPK/Sirt1 and anti-inflammatory signaling pathways.Current meta-analysis could not consistently verify the efficacy of resveratrol in treating NAFLD, but demonstrated the liver-protective effects on NAFLD. The large-sample scale and single region RCTs were further needed to investigate the efficacy.